Penciptaan Nilai Bersama (Value Co-Creation) dan Berbagi Pengetahuan (Knowledge Sharing) pada Terbentuknya Inovasi Perusahaan Inti dalam Kolaborasi Bisnis - Prabowo, Gilang Mukti; Lestari, Luthfi Bangun; Baskoro, Baskoro (CV. Green Publisher Indonesia, 2025)
This research aims to analyze and understand in depth how interactions in a network centered on the Core Company and its partners produce an innovation through shared value creation activities and knowledge sharing. This study used multiple case studies with qualitative analysis to examine the data generated from interviews with informants. The results of the study show that the interaction between the core company and its partners can trigger the emergence of innovation in each unit. In this study, the unit of analysis used is a feedback loop process between the core company and its partners. Based on the results of the research, it was also found that there is a difference in the results of innovation between partner levels, where the larger the partner, the better the innovation produced. Further research is expected to analyze these findings, where the organizational structure affects the results of the innovations carried out.